Plants and animals share functionally common bacterial virulence factors - Rahme, Laurence G. (The National Academy of Sciences, 2000)
By exploiting the ability of Pseudomonas aeruginosa to infect a variety of vertebrate and nonvertebrate hosts, we have developed model systems that use plants and nematodes as adjuncts to mammalian models to help elucidate the molecular basis of P. aeruginosa pathogenesis. Our studies reveal a remarkable degree of conservation in the virulence mechanisms used by P. aeruginosa to infect hosts of divergent evolutionary origins.